Foreword - Luigi Dei (JLIS.it, 2018)
Good morning to everybody, I am very happy to be here and to give the best greetings and wishes of the University of Florence to this important and very interesting Meeting on Resource Description and Access in Europe: a reality and a challenge. You will discuss about themes extremely associated to current events in a context which is always more global and against single nationalisms. You know very well that the information network and environment are rapidly evolving often in unexpected ways. Therefore, the question of writing of an international cataloguing code appears a strong need and at the same time an extraordinary challenge. The theme is not only practical but it assumes a more general relevance: it’s the topic of assuring cultural diversity. Cultural diversity is protected also by the easy understanding bibliographic and authority information. The digital-informatics revolution has created a truly globalised world where differences remain, but they are strongly interconnected. This interconnection needs to reflect about national codes in a global context. If we can imagine the possibility of local adjustments in an international recognised code, we cannot guess that every country goes in its own direction. It would not lead to a valorisation of the cultural diversities but rather to a terrible confinement of cultures in single, not communicating corners. If we translate this argument to Italy, I believe we can conclude as Mauro Guerrini states in his notes to this event: it is more useful and preferable to participate in the drafting international guidelines, namely, RDA, bringing our rich cultural heritage and our Italian cataloguing background and perspective to an international dimension. Often people argue that the international dimension suffers the limit to kill diversities and cultural roots. I don’t think this is a real risk. Internationalisation succeeds in transmitting to other people our diversities and cultural roots and at the same time allows to every culture to dialogue with the others discovering how wonderful is the world. I believe that the invitation to create bridges and breaking walls is the key word of the present and future times. But bridges, if you carefully meditate, are structures that connect two different sides and they need to be made with something which be common to both sides. In your field I guess that RDA and internationally recognised codes are the correct bridges to connect not only two sides but many and many different sides. Leaving national codes is equivalent to lifting walls of not communication and intellectuals cannot think that a world with less communication is better. Thank you so much of your attention and my best wishes for the success of this meeting and of your studies.